(untitled) (Chest & Heart Journal, 2021)
Introduction: Cotton textile mill is one of the largest sectors providing a prominent source of growth in the rapidly developing economy of Bangladesh. This sector employs about 5 million workers of whom the majority (80%) are the women. During the processing from fiber to fabric, the workers are constantly at risk of suffering from various respiratory problems. The study was carried out to evaluate the association of long-term exposure to organic cotton dust with different respiratory symptoms in the workers. Based on the results, the study may provide information on respiratory health risks and finally, the data can be used to help the policymakers in executing appropriate strategy regarding the work environment. Materials and Methods: This cross-sectional study was conducted in a cotton mill at Gazipur, Dhaka, Bangladesh for 1 year. Three hundred and eighty- four workers had participated in this study. Inquiry was made regarding respiratory symptoms with the help of a pretested questionnaire. An air quality monitor was used to measure the amount of dust (PM 2.5) in the workplace. Results: 73.18% of workers had one or more respiratory symptoms, 54.2% had cough, 31.8% had phlegm production. Breathlessness was complained by 27.9%, chest tightness by 24.2% and wheezing by 14.3%. Only one upper respiratory tract symptom was considered which was runny nose; 47.1% of workers reported about it. The blow room workers were more affected (47%) in comparison to ring and packaging room workers. Working section had significant association with respiratory symptoms. Using biomass fuel came out as a potential confounding factor. Most importantly, it was demonstrated that the level of PM 2.5 varied in the different working sections based on activities of the processing of cotton, and it significantly had a greater impact on respiratory symptoms. Conclusion: The prevalence of respiratory symptoms was higher among the workers exposed to cotton dust. Working section, level of PM 2.5 and use of biomass fuel in some respondents are some of the significant risk factors for the presence of symptoms. Chest Heart J. 2020; 44(1) : 13-19